ACTIVITIES OF FEMALE SCIENTISTS, SCHOLARS IN THE RESEARCH OF TIMUR STUDIES: CHRONOLOGY AND EDUCATION - Yakhshieva Zebo Rashidovna (KONFERENSIYALAR, 2025)
Abstract. In this thesis compared the scientific and historical research conducted on the great Uzbek conqueror Sahibkiran Amir Temur. In Particular, Sh. Sh. Alauyeva’s scientific study which is enlightened views of Amir Temur brought to a certain sequence the views advanced in the works of other scholars and Orientalists from her target. We tried to make new scientific conclusions on the basis of cross-examination of scientific research, chronological, typological comparison.